Phenolic Composition and Antioxidant and Antihemolytic Activities of the Dichloromethane and Ethyl Acetate Fractions from Tipuana tipu (Benth.) Leaves - Mendanha Cruz, Thiago; Kutzmy, Ana Laiza; Stelle, Yasmin; Sousa Santos, Jânio; Granato, Daniel; Sávio Nunes, Domingos; Boscacci Marques, Mariza (Orbital: The Electronic Journal of Chemistry, 2025)
The Tipuana tipu is a leguminous tree employed in popular medicine for its healing and anti-inflammatory properties. This study aimed to assess the antioxidant activity and bioactivity of fractions of the crude extract from the T. tipu leaves. The chemical composition, antioxidant activity, lipid peroxidation inhibition and antihemolytic activity were assessed on the dichloromethane and ethyl acetate (pH 4 and 8) fractions of the crude extract obtained from T. tipu leaves. The fractions presented significant antioxidant activity (IC50 DPPH = 246, 185 and 244 mg/L for dichloromethane, ethyl acetate at pH 8 and ethyl acetate at pH 4, respectively), protection against lipid peroxidation (inhibition of 10-81%) and hemoprotective properties in hypotonic conditions (H50, Control = 0.45%; H50, dichloromethane = 0.41%; H50, ethyl acetate pH 8 = 0.36%; H50, ethyl acetate pH 4 = 0.37%), as well as inhibiting hemolysis in oxidative conditions (between 23-30%).